2011
DOI: 10.1007/s11096-011-9508-z
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, types and severity of medication use-related problems among medical outpatients in Nigeria

Abstract: Potentially harmful medication use-related problems are frequently encountered among medical outpatients in Nigeria. The institutionalization of medication use review and the devolution of this task to pharmacists may prove beneficial in optimizing outcomes of medication use in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…While this statistic is relatively new, we chose to report it because we felt it more accurately reflected the true agreement in our study, as many of the answers to bleeding symptoms on the Condensed MCMDM‐1VWD did not have equal distributions. Other researchers have addressed the same issue and support the use of Gwet's AC1 as a measure of inter‐rater reliability .…”
Section: Discussionmentioning
confidence: 99%
“…While this statistic is relatively new, we chose to report it because we felt it more accurately reflected the true agreement in our study, as many of the answers to bleeding symptoms on the Condensed MCMDM‐1VWD did not have equal distributions. Other researchers have addressed the same issue and support the use of Gwet's AC1 as a measure of inter‐rater reliability .…”
Section: Discussionmentioning
confidence: 99%
“…Most recently published articles that have assessed inter-rater reliability have used Cohen’s Kappa exclusively [19-26], and a recent review of the current methods used for inter-rater reliability does not even mention AC1 [27]. During our research of PubMed (up to February 2013), we found only 2 published articles that mention using Gwet’s AC1 method as part of a study [28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…found that ‘wrong drug’, ‘need for additional drug’ and ‘taking too little of the drug’ were the most frequent TRPs. A study conducted in Nigeria identified ‘nonadherence’ and ‘adverse drug reactions’ as the main TRPs …”
Section: Discussionmentioning
confidence: 99%